Foreign Investment, Corporate Ownership, and Development : Are Firms in Emerging Markets Catching Up to the World Standard? - Klara Z. Sabirianova; Jan Svejnar; Katherine Terrell (Institute for the Study of Labor (IZA), 2005)
Economic development implies that the efficiency of firms in developing countries is approaching that of firms in advanced economies. We examine the extent of this convergence in the Czech Republic and Russia, economies that represent alternative models of implementing development policies, often referred to as the Washington Consensus, that have promoted privatization, competition and foreign investment. We also test hypotheses positing that only firms near the efficiency frontier benefit from these policies and catch up. Using 1992-2000 panel data on virtually all industrial firms in each country, we find that privatization to domestic owners did not markedly improve the efficiency of firms; domestic firms are not catching up to the (world) efficiency standard given by foreign-owned firms; and the distance of the Russian firms to the efficiency frontier is much larger than that of the Czech firms and continued to grow for most firms beyond 1997 while remaining constant in the Czech Republic. Domestic firms closer to the frontier are not more likely to catch up than firms further from the frontier although foreign firms do exhibit this behavior. Foreign-owned firms are increasingly displacing domestic firms in the top deciles of the overall distribution of efficiency, due in part to slower ?learning? by domestic firms, higher efficiency of foreign startups, and foreigners? acquisitions of more efficient domestic firms. The Washington Consensus policies have not enabled domestic firms in either country to start catching up to the world standard.
Keywords: C33; L20; G32; D20; 330; efficiency; productivity; economic development; foreign direct investment; ownership; convergence; frontier; Czech Republic; Russia; Privatisierung; Direktinvestition; Produktivität; Wirtschaftliche Effizienz; Entwicklungskonvergenz; Entwicklungsstrategie; Tschechische Republik; Russland